SYNTHESIS OF POTENTIALLY BIOLOGICALLY ACTIVE SPYROHETEROCYCLIC COMPOUNDS VIA CARBOCYCLIC REFORMATSKY REAGENTS - Kirillov, N.F.; Nikiforova Е.А.; Baybarodskikh, D.V.; Zelina, E.Yu.; Machmudov, R.R. (Perm Federal Research Centre Journal, 2017)
Synthesis of spyroheterocyclic products via the interaction of carbocyclic Reformatsky reagents with electrophilic substrates, such as carbonyl and carbonyl-containing compounds, α,β- unsaturated carbonyl compounds and amides, as well as anhydrides of dicarboxylic acids was studied during the research. Spyroheterocyclic structures are formed via cyclisation of intermediates, produced by addition of Reformatsky reagents to electrophiles.